Effect of encapsulation on β-carotene absorption and metabolism in mice. (December 2021) - Chen, Ling; Yokoyama, Wallace; Alves, Pricilla; Tan, Yuqing; Pan, James; Zhong, Fang
Abstract: Encapsulation has been used extensively as a strategy to effectively deliver β -carotene and other bioactive compounds with low aqueous and lipid solubility to enhance its bioavailability. However, few studies have investigated the effects of particle size and the presence of lipids on the translocation, absorption and metabolism of nutrients in vivo . Mice were orally administered β -carotene encapsulated by whey protein isolate formulations in nano- and macroscale particles, and with (emulsion) or without lipids (particle). β -carotene and its metabolized Vitamin A products were quantified in the chyme and tissues of the digestive tract (stomach, intestine, cecum) as well as liver, adipose and blood. Free β -carotene in oil-dispersion largely remained in the stomach (71.22%) or cecum (11.27%). Smaller sized emulsions improved the transition (from 5.45% to 38.35% for nanoemulsion and 58.70% for nanoparticle) and absorption (from 9.01% to 45.09% for nanoemulsion and 25.34% for nanoparticle) of β -carotene in the small intestine. Nano-emulsions were more likely to convert β -carotene into retinol or retinyl palmitate and stored in the liver, while the nanoparticles transported more β -carotene into the systemic circulation that were stored in adipose tissues. These in vivo results were compared to previous in vitro studies of whey protein isolate in Caco-2 cells and provide a comprehensive understanding about the mechanism of the biological activity of nutrients in different carriers in vivo . Graphical abstract: Image 1 Highlights: The morphology of nanoparticle and nanoemulsion during gastro-intestinal digestion in vivo was investigated. The effects of the particle size on the transition of carriers in the digestive tract and the subsequent absorption behavior of embedded β -carotene were studied. The effects of the existing oil on the transition of carriers in the digestive tract and the subsequent absorption, metabolism and distribution behavior of embedded β -carotene were explored.